Human Movement Responses to the Rorschach and Mirroring Activity: An fMRI Study. (January 2019) - Giromini, Luciano; Viglione, Donald J.; Pineda, Jaime A.; Porcelli, Piero; Hubbard, David; Zennaro, Alessandro; Cauda, Franco
It has been suggested that the Rorschach human movement (M) response could be associated with an embodied simulation mechanism mediated by the mirror neuron system (MNS). To date, evidence for this hypothesis comes from two electroencephalogram studies and one repetitive transcranial magnetic stimulation study. To provide additional data on this topic, the Rorschach was administered during fMRI to a sample of 26 healthy adult volunteers. Activity in MNS-related brain areas temporally associated with M responses was compared with such activity for other, non-M Rorschach responses. Data analyses focused on MNS regions of interest identified by Neurosynth, a web-based platform for large scale, automated meta-analysis of fMRI data. Consistent with the hypothesis that M responses involve embodied simulation and MNS activity, univariate region of interest analyses showed that production of M responses associated with significantly greater activity in MNS-related brain areas when compared with non-M Rorschach responses. This finding is consistent with the traditional interpretation of the M code.